Pengaruh Nilai Konsumen dan Kepuasan Konsumen terhadap Loyalitas Nasabah Bank Rakyat Indonesia - Riche Fermayani; Ash Shadiq Egim; Alyani Atsarina (Jurnal Ecogen, 2021)
This study aims to determine the effect of consumer value and customer satisfaction on customer loyalty at Bank BRI Unit Balai Selasa, Painan Branch. The sample studied in this study were 98 respondents who were customers of Bank BRI Unit Balai Selasa, Painan Branch. Based on the statistical t test conducted, it can be concluded that the consumer value variable has a positive and significant effect on customer loyalty, which is indicated by a significance value of 0.048 < alpha 0.05. Based on the statistical t test conducted, it can be concluded that customer satisfaction has a positive and significant effect on customer loyalty, which is indicated by a significance value of 0.000 < alpha 0.05. Based on the simultaneous f-test, a significance value of 0.000 <0.05 was obtained, it can be concluded that consumer value and overall customer satisfaction have a significant effect on customer loyalty at the BRI Bank Office Unit Balai Selasa, Painan Branch. The magnitude of the influence of the independent variable on the dependent variable is 79.3%, the remaining 20.7% is influenced by other variables that are not included in the research model.Keyword: Consumer Value, Consumer Satisfaction and Customer Loyalty.